The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.4142/jvs.2018.19.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hoof kinetics and kinematics at walk in response to hoof trimming: pressure plate assessment

Abstract: Appropriate hoof preparation and symmetry are linked to the well-being of the horse. Previous studies have shown the efficacy of pressure plates (PPs) in delivering objective biomechanical analysis. We aimed to assess the effect of hoof trimming on hoof biomechanics using a PP. Nine clinically sound Arabian horses were walked across a PP while foot strike was recorded by a digital camera. Kinetic and kinematic parameters were recorded before and after trimming. Changes were considered significant when p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Gait asymmetries were assessed using a pressure mat system that reliably measures peak pressures and maximum forces in humans 40 and other large animal models. 10,21 Given that the adult Yucatan minipig is of similar size and weight to an adult human, the pressure mat was appropriate to measure the same parameters used in human studies. The porcine model was also well suited for this project given the anatomic and biomechanical similarities between the pig and human.…”
Section: Discussionmentioning
confidence: 99%
“…Gait asymmetries were assessed using a pressure mat system that reliably measures peak pressures and maximum forces in humans 40 and other large animal models. 10,21 Given that the adult Yucatan minipig is of similar size and weight to an adult human, the pressure mat was appropriate to measure the same parameters used in human studies. The porcine model was also well suited for this project given the anatomic and biomechanical similarities between the pig and human.…”
Section: Discussionmentioning
confidence: 99%
“…Trimming and shoeing influence not only the morphology of the hooves [2,5,6] but also their balance [7]. In addition, correlations between hoof morphometric changes with stride length and with changes in joint angles [8][9][10][11][12] are described. Even so, there is little information relating to changes in joint angles and possible correlations with hoof measurements attributed to trimming.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that animal gait analysis using the pressure-sensing walkway system is less time consuming and is especially useful for repeated gait assessments (15). In addition, previous animal gait studies have utilized the pressure-sensing walkway system and validated the methodology for use with multiple species such as horses, goats, sheep, dogs, cats, and Sprague Dawley rats (16)(17)(18). However, such sensor systems have not been validated for use with the rhesus monkey, and the corresponding gait measurements have not been investigated.…”
Section: Introductionmentioning
confidence: 99%